2000
DOI: 10.1053/jhep.2000.7437
|View full text |Cite
|
Sign up to set email alerts
|

Viral clearance in hepatitis C (1b) infection: Relationship with human leukocyte antigen class II in a homogeneous population

Abstract: Hepatitis C virus (HCV) infection is the main cause of non-A, non-B hepatitis. 1-5 HCV consists of a heterogeneous mix of isolates defined by genotype, each of which is further classified into subtypes. 6,7 A number of factors have been considered in terms of their potential to predict the outcome of the disease. These include age of infection, viral typesubtype, quasispecies, viral load, and mode of infection. [8][9][10][11][12][13] Clinical heterogeneity in disease progression may reflect viral heterogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 43 publications
3
52
2
Order By: Relevance
“…An association has been reported for HLA-DRB1*0101 with self-limiting infection in this cohort. 19,26 Thio et al 41 also observed an effect for DRB1*0101.…”
Section: Susceptibility To Persistent Hcv Infectionmentioning
confidence: 89%
“…An association has been reported for HLA-DRB1*0101 with self-limiting infection in this cohort. 19,26 Thio et al 41 also observed an effect for DRB1*0101.…”
Section: Susceptibility To Persistent Hcv Infectionmentioning
confidence: 89%
“…Association of DQB1*0301 allele with natural clearance of HCV is mentioned by many authors in original studies and reviews (10,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The other allele described as being important in patients who clear HCV spontaneously is DRB1*1101 (13,16,18,(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studies of women who were accidentally infected with the same inoculum (contaminated immunoglobulin D antibody) showed that despite receiving the same virus strain, viral diversity could not account for the dichotomy in outcome (clearance versus persistence). [29][30][31][32][33] Thus, differences in the host response were more likely to be the determining factor. Several important insights into this crossroad of viral and host genetics have been forthcoming from studies in human immunodeficiency virus (HIV) infection.…”
Section: Introductionmentioning
confidence: 99%